Inferences on the Geological History Through Soil Minerology, Palakkad Gap Region, South India - Peedamparammal, Jincy; Pangunny, Pankajakshan; Chandran, Ramachandran; Sajikumar, Jeena Beena; Chothodi, Sathish; Vijayan, Dhanya; Scaria, Richard (Journal of Geographical Sciences and Education, 2025)
This study assess soil mineralogy and prevailing weathering conditions within the Palakkad Gap, 22 surface soil samples (0–25 cm depth) were collected based on geology, geomorphology, lineament patterns, and land use. Samples were analyzed using X-ray diffraction (XRD; model 600) to determine mineralogical composition (Moore & Reynolds, 1997). The diffraction patterns indicated the presence of quartz, feldspar, kaolinite–illite, gibbsite, goethite, mica, chlorite, calcite, and vermiculite. Quartz and feldspar were interpreted as lithogenic minerals derived from the parent rock, whereas kaolinite, gibbsite, and goethite represent pedogenic weathering products formed under variable pH regimes. Thin-section petrography revealed altered feldspar margins and fractures infilled with Fe-oxides, indicating early to moderate stages of chemical weathering. Mineralogical assemblages in the Palakkad Gap reflect the combined effects of lithology, climate, and geomorphic processes on soil and landscape evolution (Ollier & Pain, 1996; Birkeland, 1999).